Associations of attachment avoidance and anxiety with life satisfaction, satisfaction with singlehood, and desire for a romantic partner. Issue 1 (23rd December 2021) - MacDonald, Geoff; Park, Yoobin
Abstract: Living single is becoming increasingly common worldwide and understanding within‐group predictors of well‐being among singles is becoming a stronger research priority. Although Pepping, MacDonald, and Davis suggested individual differences in attachment security may be useful for predicting singles' well‐being, there are no published data on the issue. In this research, single participants ( N = 1930; 49% men; M age = 31 years; 75% White) completed measures of attachment security as well as measures of life satisfaction, satisfaction with singlehood, and desire for a romantic partner. The data suggested that higher levels of attachment avoidance and attachment anxiety were both associated with lower levels of life satisfaction as well as satisfaction with singlehood. However, when controlling for life satisfaction, attachment avoidance was not associated with satisfaction with singlehood. We also found that higher levels of attachment avoidance were associated with less desire for a romantic partner whereas higher levels of attachment anxiety were associated with stronger desire for a partner. Our findings suggest that individual differences in attachment security may indeed be useful in predicting well‐being‐related outcomes for singles.